Composition and Principles of Pedagogical Competence in the Educational Process - Yulduz Xayrullakizi Hudoyberdiyeva; Ikromjon Gulomjonovich Tursunov (Academia One Publishing, 2023)
The article examines the structure and principles of pedagogical competence in the educational system, briefly analyzes and discusses it
Keywords: competence; professional competence; qualities of professional competence; pedagogical professional competence